Eksistensi Pno Adeak Naik Haji pada Masyarakat Kerinci: Menggali Nilai-Nilai Sosial untuk Generasi Mendatang - Lovendo, Tomy (Sosial Budaya, 2024)
This study examines the Pno Adeak tradition in the hajj ceremony of the Kerinci community, which holds significant social values and is still maintained to this day. This tradition is a rhythmic dialogue between the host and the guest, represented by traditional leaders, encompassing the expression of intentions, purposes, and requests for permission. Pno Adeak is considered important in various traditional ceremonies such as weddings, kenduri sko, kenduri sudah nue, funerals, healing ceremonies, new house inaugurations, and hajj departures. Its existence demonstrates the commitment of the Kerinci community to preserving cultural heritage amidst the wave of modernization. This research employs a qualitative method with a phenomenological approach to understand how the community interprets the social and spiritual values within the tradition and how these values contribute to the sustainability of the tradition in modern society. The results show that social values such as empathy, politeness, and responsibility embedded in Pno Adeak are crucial in maintaining social order and cultural identity of the Kerinci community